Investigation into rolling contact fatigue and wear of high-speed train wheels on long steep slope track - ZHOU Chen; ZHENG Jing; QIAO Qingfeng; ZOU Xiaolong; CHEN Jiaming; TAO Gongquan (机车电传动)
A rolling contact fatigue prediction model and a wear prediction model were established to analyze the influence of slope and speed on the rolling contact fatigue and wear of electric multiple unit (EMU) wheels on long steep slope track. The wheel rolling contact fatigue prediction model was composed of a vehicle dynamics model and a damage function. The wheel wear prediction model included a vehicle dynamics model, a wheel-rail local contact model, a wear model, and smoothing and updating strategy. The wheel wear prediction model was modified and verified based on the field measured wheel wear results. The results show that downhill is the main case of wheel rolling contact fatigue, and the higher the speed or downhill slope, the more likely the wheel initiate rolling contact fatigue. When the vehicle runs in a straight line, the fatigue crack initiation position is basically within the range of 6 to 9 mm from the outside of the nominal rolling circle of the wheel, and the fatigue crack initiation angle is basically between -10° to10°. Whether uphill or downhill, the greater the slope, the greater the wheel wear. The wear area of the wheels on an uphill condition with a slope of 30‰ is approximately 1.85 times that of a downhill condition with a slope of ‒30‰. Under the same slope conditions, for uphill cases, wheel wear increases with the increase of vehicle speed; for downhill cases, vehicle speed has less effect on wheel wear.